2016
DOI: 10.4103/1008-682x.160883
|View full text |Cite
|
Sign up to set email alerts
|

Identification of late-onset hypogonadism in middle-aged and elderly men from a community of China

Abstract: In this study, we investigated the essential criteria for late-onset hypogonadism (LOH) syndrome based on the presence of symptoms associated with low testosterone levels in Han Chinese men. Blood tests for total testosterone (TT) and sex hormone–binding globulin (SHBG) were performed, and the aging male symptoms (AMS) questionnaire was conducted in a randomly selected cohort composed of 944 Chinese men aged 40 to 79 years from nine urban communities. Three sexual symptoms (decreased ability/frequency of sexua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 40 publications
(72 reference statements)
0
12
0
Order By: Relevance
“…Study exclusion criteria were based on reports from previous studies [ 16 ]. Additionally, criteria for this study are identical to other, ongoing studies in China [ 31 ]; this intentional design will improve our ability to compare results across the entire country in the future. Inclusion criteria were male sex, age between 20–89 years, and residence in one of the communities selected for inclusion in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Study exclusion criteria were based on reports from previous studies [ 16 ]. Additionally, criteria for this study are identical to other, ongoing studies in China [ 31 ]; this intentional design will improve our ability to compare results across the entire country in the future. Inclusion criteria were male sex, age between 20–89 years, and residence in one of the communities selected for inclusion in this study.…”
Section: Methodsmentioning
confidence: 99%
“…The overall prevalence of LOH in the EMAS study population would be 2.1% (1.2% moderate LOH and 0.9% severe LOH) and increased with age from 0.1% to 5.1%. A study ( Liu et al, 2016 ) identified that TT levels <13.21 nmol/L or cFT <268.89 pmol/L were associated with an increase in the three sexual symptoms (decreased ability/frequency of sexual activity, decreased number of morning erections, and decreased libido). The prevalence of LOH was 9.1% under these criteria, including all three sexual symptoms with the aforementioned TT and cFT cutoff.…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies on LOH in Chinese subjects over the past decade still had some shortcomings. For example, statistical analyses of data were lacking as well as reports on classification of TD ( He et al, 2012 ; Li et al, 2005 ; Liu et al, 2016 ; Sun et al, 2012 ; Wu et al, 2013 ; Zhou et al, 2010 ).…”
mentioning
confidence: 99%
“…It is commonly accepted that LUTS in older men are more prevalent than younger men [ 11 ]. With aging, a significant percentage of men develop late-onset hypogonadism (LOH), which is characterized by a deficiency in testosterone levels [ 40 ]. Taken together, higher level of TT and FT in older men may play a protective role for LUTS status in a complex way which is still unclear and need further investigation.…”
Section: Discussionmentioning
confidence: 99%